Wiedźmą być. Kobiece motywy inicjacyjne w polskiej literaturze popularnej XXI wieku - Grażyna Lasoń-Kochańska (Literatura i Kultura Popularna)
In recent years Polish literature and popular culture have been increasingly populated by witches. Many authors use the historical, folk image of an ambivalent pagan witch as basis for creating their characters. Other notable sources are fairy tales, feminism (after all the myth of the witch was popularized by second-wave feminism) and neopaganism (women as priestesses of nature). As a result of these various inspirations depictions of the witch are quite diverse, while the plot patterns presented in terms of stages of initiation are characterized by high constancy. A young girl, entering adulthood, not knowing who she is — such is the protagonist of many a novel. Her fictional biography begins with ‘borderline events’: an important birthday, a graduation, inheriting a farmhouse (usually from her grandmother). After crossing this narrative threshold, the protagonist is imbued with the powers of a witch, which she initially rejects. An elderly woman — her guide — persuades her to accept them. She teaches her the how to notice the manifestations of femininity that have been suppressed in our culture, and were represented as witches, fortune-tellers and madwomen. The use of magic is shown as a rediscovery of these rejected abilities, wrongly labeled as insane. It seems that the most important values related to the witch’s initiation motive are: restoring the relationship with the creative female element (intuition, nature, imagination), repairing generational ties between women (an older kinswoman as the master of initiation) and putting emphasis on female spirituality.